GEN-13 PAIRED MUTATIONAL ANALYSIS IN SECONDARY NERVOUS SYSTEM LYMPHOMA AND PCNSL SYSTEMIC RELAPSE REVEALS DRIVER MUTATION CANDIDATES IN THE CENTRAL NERVOUS SYSTEM. (3rd December 2022) - Sasaki, Nobuyoshi; Kume, Satoshi; Tateishi, Kensuke; Nakamura, Taishi; Ibayashi, Kenji; Yamagishi, Yuki; Saito, Kuniaki; Kobayashi, Keiichi; Matsushita, Yuko; Hibiya, Yuko; Kitahara, Mai; Suzuki, Saki; et al.
Abstract: Primary central nervous system lymphoma (PCNSL) is an aggressive extranodal non-Hodgkin lymphoma confined to the brain, eyes, and the spinal cord. The mechanism of central nervous system (CNS) tropism in PCNSL has not been fully elucidated. Diffuse large B cell lymphomas (DLBCLs) occasionally present with distant recurrence, which can involve inside and outside the CNS. Secondary central nervous system lymphomas (SCNSLs) are CNS relapse of systemic lymphoma. PCNSLs also rarely present with systemic relapse. We have previously reported in our study of whole exome sequencing that PCNSLs harbor frequent mutations in genes of B cell receptor pathway members and aberrant somatic hypermutation (aSHM) target genes. Although several genetic alterations were identified as more frequent in PCNSLs compared with systemic lymphomas, specific genetic alterations which serve as the driver for CNS tropism in PCNSLs has not been identified. In order to search for mutations which might serve as driver mutations in the CNS, we have performed targeted sequencing in paired samples from patients with recurrent lymphomas, either SCNSLs or PCNSL systemic relapses, using Ion Torrent multiplex PCR. Mutational profiles were compared between the primary and recurrent tumor. Six cases (four SCNSL cases and two PCNSL systemic relapse cases) were analyzed. Of note, in the SCNSL cases, several de novo mutations were enriched only among the recurrent CNS tumors. Among these mutations, BTG2 mutations were observed in 3/4 (75%), and B2M and KLHL14 mutations were observed in 2/4 (50%) cases. In the two PCNSL systemic relapse cases, KMT2D mutations were enriched only in the recurrent systemic tumors. It is suggested that these de novo mutations in the recurrent CNS tumors might serve as driver mutations in the CNS. Further analysis in larger cohorts, and functional studies are required in order to validate these findings.